The Influence of Product Quality, Outlet Location, and Price Competition on Interest to Buy Yanti Fried Chicken Rantauprapat - Diki Salvador; Elida Florentina Sinaga Simanjorang; Abd. Halim (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
In the culinary industry, especially fast food, there are several factors that can influence consumer buying interest. Product quality is an important factor in influencing consumer buying interest. High-quality flour fried chicken, with a crispy texture on the outside and soft and juicy meat on the inside, will increase consumer satisfaction. The existence of outlets that are strategic and easy to reach by potential consumers will increase the possibility of consumers buying fried chicken with flour. Price competition can also affect consumer buying interest. If the price of flour fried chicken is relatively lower or more competitive compared to other competitors, consumers tend to prefer to buy that product. This research was conducted with the aim to determine the effect of product quality, outlet location, and price competition on the buying interest of Yanti Fried Chicken flour fried chicken. In this study, the results showed that the quality of Yanti Fried Chicken flour fried chicken, outlet location, and Price competition for fried chicken with flour, both partially and simultaneously, have a significant influence on consumer buying interest in Yanti Fried Chicken’s flour fried chicken.